Rapid solubility and mineral storage of CO2 in basalt - Gislason, S.; Broecker, W.; Gunnlaugsson, E.; Snaebjornsdottir, S.; Mesfin, K.; Alfredsson, H.; Aradottir, E.; Sigfusson, B.; Gunnarsson, I.; Stute, M.; Matter, J.; Arnarson, M.; et al. (Elsevier, 2014)
The long-term security of geologic carbon storage is critical to its success and public acceptance. Much of the security risk associated with geological carbon storage stems from its buoyancy. Gaseous and supercritical CO2 are less dense than formation waters, providing a driving force for it to escape back to the surface. This buoyancy can be eliminated by the dissolution of CO2 into water prior to, or during its injection into the subsurface. The dissolution makes it possible to inject into fractured rocks and further enhance mineral storage of CO2 especially if injected into silicate rocks rich in divalent metal cations such as basalts and ultra-mafic rocks. We have demonstrated the dissolution of CO2 into water during its injection into basalt leading to its geologic solubility storage in less than five minutes and potential geologic mineral storage within few years after injection [1–3]. The storage potential of CO2 within basaltic rocks is enormous. All the carbon released from burning of all fossil fuel on Earth, 5000 GtC, can theoretically be stored in basaltic rocks [4].